5.1.16 Problems 1501 to 1600

Table 5.31: First order ode

#

ODE

Mathematica

Maple

4247

\[ {}y^{\prime } = \sin \left (x -y+1\right )^{2} \]

4248

\[ {}y^{\prime } = \frac {x +y+4}{x -y-6} \]

4249

\[ {}y^{\prime } = \frac {x +y+4}{x +y-6} \]

4250

\[ {}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0 \]

4251

\[ {}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0 \]

4252

\[ {}y-x^{3}+\left (y^{3}+x \right ) y^{\prime } = 0 \]

4253

\[ {}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime } \]

4254

\[ {}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0 \]

4255

\[ {}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0 \]

4256

\[ {}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right ) \]

4257

\[ {}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0 \]

4258

\[ {}1+y+\left (1-x \right ) y^{\prime } = 0 \]

4259

\[ {}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0 \]

4260

\[ {}1 = \frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}} \]

4261

\[ {}\left (3 x^{2}-y^{2}\right ) y^{\prime }-2 x y = 0 \]

4262

\[ {}x y-1+\left (x^{2}-x y\right ) y^{\prime } = 0 \]

4263

\[ {}\left (x +3 y^{4} x^{3}\right ) y^{\prime }+y = 0 \]

4264

\[ {}\left (x -1-y^{2}\right ) y^{\prime }-y = 0 \]

4265

\[ {}y-\left (x +x y^{3}\right ) y^{\prime } = 0 \]

4266

\[ {}x y^{\prime } = x^{5}+y^{2} x^{3}+y \]

4267

\[ {}\left (x +y\right ) y^{\prime } = y-x \]

4268

\[ {}x y^{\prime } = y+x^{2}+9 y^{2} \]

4269

\[ {}x y^{\prime }-3 y = x^{4} \]

4270

\[ {}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}} \]

4271

\[ {}2 x y+\left (x^{2}+1\right ) y^{\prime } = \cot \left (x \right ) \]

4272

\[ {}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2} \]

4273

\[ {}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right ) \]

4274

\[ {}2 y-x^{3} = x y^{\prime } \]

4275

\[ {}\left (1-x y\right ) y^{\prime } = y^{2} \]

4276

\[ {}2 x +3 y+1+\left (2 y-3 x +5\right ) y^{\prime } = 0 \]

4277

\[ {}x y^{\prime } = \sqrt {x^{2}+y^{2}} \]

4278

\[ {}y^{2} = \left (x^{3}-x y\right ) y^{\prime } \]

4279

\[ {}x^{2} y^{3}+y = \left (y^{2} x^{3}-x \right ) y^{\prime } \]

4280

\[ {}x y^{\prime }+y = x \cos \left (x \right ) \]

4281

\[ {}\left (x y-x^{2}\right ) y^{\prime } = y^{2} \]

4282

\[ {}\left ({\mathrm e}^{x}-3 x^{2} y^{2}\right ) y^{\prime }+y \,{\mathrm e}^{x} = 2 x y^{3} \]

4283

\[ {}x^{2}+y = x y^{\prime } \]

4284

\[ {}x y^{\prime }+y = x^{2} \cos \left (x \right ) \]

4285

\[ {}6 x +4 y+3+\left (3 x +2 y+2\right ) y^{\prime } = 0 \]

4286

\[ {}\cos \left (x +y\right )-x \sin \left (x +y\right ) = x \sin \left (x +y\right ) y^{\prime } \]

4287

\[ {}y^{2} {\mathrm e}^{x y}+\cos \left (x \right )+\left ({\mathrm e}^{x y}+y \,{\mathrm e}^{x y} x \right ) y^{\prime } = 0 \]

4288

\[ {}y^{\prime } \ln \left (x -y\right ) = 1+\ln \left (x -y\right ) \]

4289

\[ {}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}} \]

4290

\[ {}y^{2}-3 x y-2 x^{2} = \left (x^{2}-x y\right ) y^{\prime } \]

4291

\[ {}2 x y+\left (x^{2}+1\right ) y^{\prime } = 4 x^{3} \]

4292

\[ {}{\mathrm e}^{x} \sin \left (y\right )-y \sin \left (x y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )-x \sin \left (x y\right )\right ) y^{\prime } = 0 \]

4293

\[ {}\left (y-x^{2}+x \,{\mathrm e}^{y}\right ) y^{\prime } = 2 x y-{\mathrm e}^{y}-x \]

4294

\[ {}{\mathrm e}^{x} \left (1+x \right ) = \left (x \,{\mathrm e}^{x}-y \,{\mathrm e}^{y}\right ) y^{\prime } \]

4295

\[ {}2 x y+x^{2} y^{\prime } = 0 \]

4296

\[ {}x +y+\left (x -y\right ) y^{\prime } = 0 \]

4297

\[ {}\ln \left (x \right ) y^{\prime }+\frac {x +y}{x} = 0 \]

4298

\[ {}\cos \left (y\right )-x \sin \left (y\right ) y^{\prime } = \sec \left (x \right )^{2} \]

4299

\[ {}y \sin \left (\frac {x}{y}\right )+x \cos \left (\frac {x}{y}\right )-1+\left (x \sin \left (\frac {x}{y}\right )-\frac {x^{2} \cos \left (\frac {x}{y}\right )}{y}\right ) y^{\prime } = 0 \]

4300

\[ {}\frac {x}{x^{2}+y^{2}}+\frac {y}{x^{2}}+\left (\frac {y}{x^{2}+y^{2}}-\frac {1}{x}\right ) y^{\prime } = 0 \]

4301

\[ {}x^{2} \left (1+y^{2}\right ) y^{\prime }+y^{2} \left (x^{2}+1\right ) = 0 \]

4302

\[ {}x \left (x -1\right ) y^{\prime } = \cot \left (y\right ) \]

4303

\[ {}r y^{\prime } = \frac {\left (a^{2}-r^{2}\right ) \tan \left (y\right )}{a^{2}+r^{2}} \]

4304

\[ {}\sqrt {x^{2}+1}\, y^{\prime }+\sqrt {1+y^{2}} = 0 \]

4305

\[ {}y^{\prime } = \frac {x \left (1+y^{2}\right )}{y \left (x^{2}+1\right )} \]

4306

\[ {}y^{\prime } y^{2} = 2+3 y^{6} \]

4307

\[ {}\cos \left (y\right )^{2}+\left (1+{\mathrm e}^{-x}\right ) \sin \left (y\right ) y^{\prime } = 0 \]

4308

\[ {}y^{\prime } = \frac {x^{3} {\mathrm e}^{x^{2}}}{y \ln \left (y\right )} \]

4309

\[ {}x \cos \left (y\right )^{2}+{\mathrm e}^{x} \tan \left (y\right ) y^{\prime } = 0 \]

4310

\[ {}x \left (1+y^{2}\right )+\left (2 y+1\right ) {\mathrm e}^{-x} y^{\prime } = 0 \]

4311

\[ {}x y^{3}+{\mathrm e}^{x^{2}} y^{\prime } = 0 \]

4312

\[ {}x \cos \left (y\right )^{2}+\tan \left (y\right ) y^{\prime } = 0 \]

4313

\[ {}x y^{3}+\left (1+y\right ) {\mathrm e}^{-x} y^{\prime } = 0 \]

4314

\[ {}y^{\prime }+\frac {x}{y}+2 = 0 \]

4315

\[ {}x y^{\prime }-y = x \cot \left (\frac {y}{x}\right ) \]

4316

\[ {}x \cos \left (\frac {y}{x}\right )^{2}-y+x y^{\prime } = 0 \]

4317

\[ {}x y^{\prime } = y \left (1+\ln \left (y\right )-\ln \left (x \right )\right ) \]

4318

\[ {}x y+\left (x^{2}+y^{2}\right ) y^{\prime } = 0 \]

4319

\[ {}\left (1-{\mathrm e}^{-\frac {y}{x}}\right ) y^{\prime }+1-\frac {y}{x} = 0 \]

4320

\[ {}x^{2}-x y+y^{2}-x y y^{\prime } = 0 \]

4321

\[ {}\left (3+2 x +4 y\right ) y^{\prime } = x +2 y+1 \]

4322

\[ {}y^{\prime } = \frac {2 x +y-1}{x -y-2} \]

4323

\[ {}y+2 = \left (2 x +y-4\right ) y^{\prime } \]

4324

\[ {}y^{\prime } = \sin \left (x -y\right )^{2} \]

4325

\[ {}y^{\prime } = \left (1+x \right )^{2}+\left (1+4 y\right )^{2}+8 x y+1 \]

4326

\[ {}3 x^{2}+6 x y^{2}+\left (6 x^{2} y+4 y^{3}\right ) y^{\prime } = 0 \]

4327

\[ {}2 x^{2}-x y^{2}-2 y+3-\left (x^{2} y+2 x \right ) y^{\prime } = 0 \]

4328

\[ {}x y^{2}+x -2 y+3+\left (x^{2} y-2 x -2 y\right ) y^{\prime } = 0 \]

4329

\[ {}3 y \left (x^{2}-1\right )+\left (x^{3}+8 y-3 x \right ) y^{\prime } = 0 \]

4330

\[ {}x^{2}+\ln \left (y\right )+\frac {x y^{\prime }}{y} = 0 \]

4331

\[ {}2 x \left (3 x +y-y \,{\mathrm e}^{-x^{2}}\right )+\left (x^{2}+3 y^{2}+{\mathrm e}^{-x^{2}}\right ) y^{\prime } = 0 \]

4332

\[ {}3+y+2 y^{2} \sin \left (x \right )^{2}+\left (x +2 x y-y \sin \left (2 x \right )\right ) y^{\prime } = 0 \]

4333

\[ {}2 x y+\left (y^{2}+2 x y+x^{2}\right ) y^{\prime } = 0 \]

4334

\[ {}x^{2}-\sin \left (y\right )^{2}+x \sin \left (2 y\right ) y^{\prime } = 0 \]

4335

\[ {}y \left (2 x -y+2\right )+2 \left (x -y\right ) y^{\prime } = 0 \]

4336

\[ {}4 x y+3 y^{2}-x +x \left (x +2 y\right ) y^{\prime } = 0 \]

4337

\[ {}y+x \left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0 \]

4338

\[ {}x^{2}+2 x +y+\left (3 x^{2} y-x \right ) y^{\prime } = 0 \]

4339

\[ {}y^{2}+\left (x y+y^{2}-1\right ) y^{\prime } = 0 \]

4340

\[ {}3 y^{2}+3 x^{2}+x \left (x^{2}+3 y^{2}+6 y\right ) y^{\prime } = 0 \]

4341

\[ {}2 y \left (x +y+2\right )+\left (y^{2}-x^{2}-4 x -1\right ) y^{\prime } = 0 \]

4342

\[ {}2+y^{2}+2 x +2 y y^{\prime } = 0 \]

4343

\[ {}2 x y^{2}-y+\left (y^{2}+x +y\right ) y^{\prime } = 0 \]

4344

\[ {}y \left (x +y\right )+\left (x +2 y-1\right ) y^{\prime } = 0 \]

4345

\[ {}2 x \left (x^{2}-\sin \left (y\right )+1\right )+\left (x^{2}+1\right ) \cos \left (y\right ) y^{\prime } = 0 \]

4346

\[ {}x^{2}+y+y^{2}-x y^{\prime } = 0 \]